Særlige pligtforhold i den internationale strafferet - Lene Ravn (Nordisk Tidsskrift for Kriminalvidenskab)
The article considers the possibilities of prosecuting extraterritorial crimes. Pursuant to section 7 of the Danish Penal Code, crimes committed abroad by Danish citizens may be punished in Denmark on the condition that the crime is penalized at the place of commission (" double criminality"). Pursuant to sections 6 and 9, Denmark also has jurisdiction over such crimes when an effect of the crime may be localized to Denmark. Furthermore it is shown that pursuant to the protective principle (section 8(1)(1)-(2) of the Penal Code), Denmark has jurisdiction over certain extraterritorial crimes against individuals, provided that a special legal relationship exists between the perpetrator and the victim.